Peningkatan Pengetahuan Kader Posyandu dalam Manajemen Laktasi Melalui Metode Ceramah di Kelurahan Rangkapan Jaya Kecamatan Pancoran Mas Kota Depok - Nurul Huriah Astuti (UHAMKA Press, 2017)
Knowledge Improvement of Posyandu Cadres in Lactation Management Through Lecture Method in Rangkapan Jaya Village, Pancoran Mas Sub-district, Depok City Introduction : Mother's Milk is the first food for babies and provides energy and nutrients not only forthe first six months of life but also up to two years of age. Breastfeeding is one of the most effective waysto ensure the health and survival of the child. Indonesia Demographic and Health Survey 2012 states thatthe exclusive breastfeeding rate was 42% in Indonesia, 33.7% in West Java, and 61.36% in Depok City.This numbers need to be improved. One way is through health cadres in Posyandu as the front guard toimprove public health status. This study aims to determine the effectiveness of lecture methods with suchtools in improving knowledge about lactation management.Methods : The subjects of this study were 24 health cadres at four posyandu in Rangkapan Jaya VillagePancoran Mas Sub-district Depok City. This type of research is quasi experimental with pre-test andpost-test design.Results : The results showed that 87.5% of respondents had improved knowledge after training withlecture and demonstration methods with props and emo-demo techniques. The average pre-test score was85.88 and post-test score was 91.08. Respondents who had a range of knowledge score 90-100 werehigher on post-test result (62.5%) than pre-test result (29.2%). The results of statistical tests showed thatthere was difference of cadres knowledge between before and after being given lactation managementtraining through lecture and demonstration methods with props and emo-demo techniques (p = 0.004).Conclusions : The results showed that 87.5% of respondents had improved knowledge after training withlecture and demonstration methods with props and emo-demo techniques. The results of statistical testsindicate that the methods performed effectively increase the knowledge of health cadres. Continuingeducation for posyandu health cadres through lecture and demontration methods with props and emodemotechniques can bean option.